2005
DOI: 10.1074/jbc.m406509200
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Activity Relationships of Diastereomeric Lysine Ring Size Analogs of the Antimicrobial Peptide Gramicidin S

Abstract: Structure-activity relationships were examined in seven gramicidin S analogs in which the ring-expanded analog GS14 [cyclo-(VKLKVdYPLKVKLdYP)] is modified by enantiomeric inversions of its lysine residues. The conformation, amphiphilicity, and self-association propensity of these peptides were investigated by circular dichroism spectroscopy and reversed phase high performance liquid chromatography. 31 P nuclear magnetic resonance spectroscopic and dye leakage experiments were performed to evaluate the capacity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 37 publications
0
23
1
Order By: Relevance
“…4) although it is generally assumed that the principal target of GS is the membrane lipid bilayer rather than the protein components. Recent studies have shown that structural analogs of GS can be designed with markedly reduced hemolytic activity and enhanced microbial activity, suggesting the possibility of GS derivatives as potent oral or injectable broad-spectrum antibiotics [9,[20][21][22]. Our finding would provide a new insight into the molecular design and development of novel GS-based antibiotics (see Fig.…”
Section: Effects Of Gs On E Coli Respiratory Enzymes In Intact Membrmentioning
confidence: 61%
See 1 more Smart Citation
“…4) although it is generally assumed that the principal target of GS is the membrane lipid bilayer rather than the protein components. Recent studies have shown that structural analogs of GS can be designed with markedly reduced hemolytic activity and enhanced microbial activity, suggesting the possibility of GS derivatives as potent oral or injectable broad-spectrum antibiotics [9,[20][21][22]. Our finding would provide a new insight into the molecular design and development of novel GS-based antibiotics (see Fig.…”
Section: Effects Of Gs On E Coli Respiratory Enzymes In Intact Membrmentioning
confidence: 61%
“…From the screening of hundreds of natural antibiotics in the Kitasato Institute for Life Sciences Chemical Library [19], we found the inhibitory activity of GS for Escherichia coli cytochrome bd. Recent studies have shown that GS analogs can be designed with the markedly improved therapeutic index, suggesting the possibility of GS derivatives as potent broad-spectrum antibiotics [9,[20][21][22]. Our finding would provide a new insight into molecular design and development of new GS analogs.…”
Section: Introductionmentioning
confidence: 56%
“…It was determined that lipid flip-flop, membrane leakiness, and peptide translocation could not individually be related to AMP structure or charge, concluding that many factors must be involved in AMP activity which have a varying impact on membranes (Zhang et al, 2001). In a detailed investigation, it was shown that the ability of gramicidin S to differentiate between mammalian and bacterial membranes depended on many peptide parameters as well, such as solubility, beta-sheet content, self-aggregation propensity, hydrophobicity and amphiphilicity (Prenner et al, 2005). These examples illustrate how changing the properties of the model system can illuminate the interactions involved.…”
Section: Antimicrobial Peptides: Vesiclesmentioning
confidence: 99%
“…9,10 However, there is still no consensus about the principles governing the formation of pores that can assist their design. Additionally, correlation of peptide conformations with ion channel function also needs to be clarified for appropriate engineering of pore constructions.…”
mentioning
confidence: 99%
“…9,10 Therefore, effects of cationic and hydrophobic characteristics of cyclic peptides on ion conducting properties should be addressed. On the basis of these points, hydrophobic Leu or cationic/hydrophilic Lys were incorporated into Pro containing cyclic hexapeptide constructs and ion conducting properties were compared.…”
mentioning
confidence: 99%